Organic metal matrix Mil-88a nano-enzyme for joint repair in the osteoarthritis mouse model - Hu, Hao; Huang, Xu; Dai, Yankun; Zhu, Kairun; Ye, Xuwen; Meng, Shengdong; Zhang, Qing; Xie, Xueguan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: In this paper we tried to conduct a novel nanomaterial strategy to overcome osteoarthritis (OA) in a mouse model. Methods: In this regard, after synthesizing the Mil-88a nanozyme, as a certain Fe-MOF, its toxic effects were detected by CCK-8 method and live-dead staining. The OA model of mouse was constructed, and paraffin sections of joints were taken for histological evaluation. In addition, immunofluorescence and immunohistochemistry were used to identify the OA progression and OARSI was used to evaluate the OA grades. We observed that Mil-88a could be easily synthesized and has high biocompatibility. Results: We observed that Mil-88a could significantly promote the expression of OA anabolism-related genes such as Col2 and also significantly inhibit the expression of OA catabolism-related genes MMP13. Besides, we observed better OARSI score in animals treated with Mil-88a nano-enzyme loading on organic metal matrix. Discussion: Overall, Mil-88a nano-enzyme could be used as a novel strategy to treat OA.